2021
DOI: 10.3390/biom11050649
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Cerebellar Neuropathology in Classical Scrapie

Abstract: In this review, the most important neuropathological changes found in the cerebella of sheep affected by classical natural scrapie are discussed. This disease is the oldest known of a group of unconventional “infections” caused by toxic prions of different origins. Scrapie is currently considered a “transmissible spongiform encephalopathy” (due to its neuropathological characteristics and its transmission), which is the paradigm of prion pathologies as well as many encephalopathies (prion-like) that present ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…Calcium-binding protein cell phenotype analysis across a high number of representative mammalian species showed that the types of positive neurons generally coincided among species. Previous analysis indicated that these proteins have a highly phylogenetically conserved molecular structure in the brain in general and in the cerebellum in particular ( 30 , 43 , 44 ). Thus, superior colliculus and cerebellum ( Supplementary Figure 1 ) have been analyzed as positive controls, showing immunostaining properties similar to those reported for humans and other high mammals, such as the common marmoset ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Calcium-binding protein cell phenotype analysis across a high number of representative mammalian species showed that the types of positive neurons generally coincided among species. Previous analysis indicated that these proteins have a highly phylogenetically conserved molecular structure in the brain in general and in the cerebellum in particular ( 30 , 43 , 44 ). Thus, superior colliculus and cerebellum ( Supplementary Figure 1 ) have been analyzed as positive controls, showing immunostaining properties similar to those reported for humans and other high mammals, such as the common marmoset ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, because ovine disease models are less well established than rodents, there are fewer validated sheep-specific neurological and cognitive tests available. Availability of reagents specialized for use on sheep tissue, particularly antibodies, is also limited, although this is improving as studies on sheep have become more common in recent years ( 60 , 124 ). In addition, because the homology between sheep and human genomes is relatively high (>85%), often antibodies developed for use on human tissue will also bind to sheep tissue.…”
Section: Limitations Of Sheepmentioning
confidence: 99%